2018
DOI: 10.1007/s11432-017-9306-x
|View full text |Cite
|
Sign up to set email alerts
|

FVO: floor vision aided odometry

Abstract: In many indoor scenarios, such as restaurants, laboratories, and supermarkets, the planar floors are covered with rectangular tiles. We realized that the abundant parallel lines and crossing points formed by tile joints can be used as natural features to assist indoor localization, and thus we propose a novel indoor localization method for mobile robots by fusing odometry and monocular vision. The method comprises three steps. First, the heading and location of the mobile robot are approximately estimated by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The core idea of the method is how to weight multiple sensors and how to determine the correction method. Wen et al [ 156 ] combine an incremental encoder with a camera to calculate the encoder-based local position and globally update the position through the similarity of the camera to the environment. Jiang et al [ 157 ] achieved the combination of feature point cloud maps and grid maps by establishing joint error co-visual between LiDAR and the monocular camera.…”
Section: Overview Of Multi-sensor Fusion Sensing Technologiesmentioning
confidence: 99%
“…The core idea of the method is how to weight multiple sensors and how to determine the correction method. Wen et al [ 156 ] combine an incremental encoder with a camera to calculate the encoder-based local position and globally update the position through the similarity of the camera to the environment. Jiang et al [ 157 ] achieved the combination of feature point cloud maps and grid maps by establishing joint error co-visual between LiDAR and the monocular camera.…”
Section: Overview Of Multi-sensor Fusion Sensing Technologiesmentioning
confidence: 99%
“…Depending on sensors used and application scenarios, different localization algorithms for skid-steering robots have been developed in recent literature. In particular, Lv, Kang, and Qin [22] proposed a method for using images for correcting headings for skid-steering robot, while requiring parallel and perpendicular lines which mainly are suitable for human-made environments. which however did not provide detailed description of how the wheel encoder's measurements were integrated.…”
Section: Related Workmentioning
confidence: 99%
“…To prevent the robots from suffering from such non-geometric hazards, the mobile robots must have the ability of terrain classification [ 4 ]. For another example, the robotic pose estimation, calculated by the kinematics model, which includes the slip parameters decided by the traversing terrains, usually benefits a lot from robotic terrain classification, especially in the situation without reliable global positioning systems [ 5 , 6 , 7 , 8 ]. Apart from hazards avoidance and pose estimation, many existing works have demonstrated that the performances of many other robotic fundamental functions, such as energy savings, route planning, gait control, etc., can be improved significantly from an accurate terrain classification method [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%